The Urinary Glycopeptide Profile Differentiates Early Cardiorenal Risk in Subjects Not Meeting Criteria for Chronic Kidney Disease - Santiago-Hernandez, Aranzazu; Martin-Lorenzo, Marta; Gómez-Serrano, María; Lopez, Juan Antonio; Martin-Blazquez, Ariadna; Vellosillo, Perceval; Minguez, Pablo; Martinez, Paula J.; Vázquez, Jesús; Ruiz-Hurtado, Gema; Barderas, Maria G.; Sarafidis, Pantelis; et al. (International journal of molecular sciences, 2024)
Early diagnosis and treatment of chronic kidney disease (CKD) is a worldwide challenge. Subjects with albumin-to-creatinine ratio (ACR) ≥ 30 mg/g and preserved renal function are considered to be at no cardiorenal risk in clinical practice, but prospective clinical studies evidence increased risk, even at the high-normal (HN) ACR range (10–30 mg/g), supporting the need to identify other molecular indicators for early assessment of patients at higher risk. Following our previous studies, here we aim to stratify the normoalbuminuria range according to cardiorenal risk and identify the glycoproteins and N-glycosylation sites associated with kidney damage in subclinical CKD. Glycoproteins were analyzed in urine from hypertensive patients within the HN ACR range compared to control group (C; ACR < 10 mg/g) by mass spectrometry. A different cohort was analyzed for confirmation (ELISA) and sex perspective was evaluated. Patients’ follow-up for 8 years since basal urine collection revealed higher renal function decline and ACR progression for HN patients. Differential N-glycopeptides and their N -glycosylation sites were also identified, together with their pathogenicity. N-glycosylation may condition pathological protein deregulation, and a panel of 62 glycoproteins evidenced alteration in normoalbuminuric subjects within the HN range. Haptoglobin-related protein, haptoglobin, afamin, transferrin, and immunoglobulin heavy constant gamma 1 (IGHG1) and 2 (IGHG2) showed increased levels in HN patients, pointing to disturbed iron metabolism and tubular reabsorption and supporting the tubule as a target of interest in the early progression of CKD. When analyzed separately, haptoglobin, afamin, transferrin, and IGHG2 remained significant in HN, in both women and men. At the peptide level, 172 N-glycopeptides showed differential abundance in HN patients, and 26 showed high pathogenicity, 10 of them belonging to glycoproteins that do not show variation between HN and C groups. This study highlights the value of glycosylation in subjects not meeting KDIGO criteria for CKD. The identified N-glycopeptides and glycosylation sites showed novel targets, for both the early assessment of individual cardiorenal risk and for intervention aimed at anticipating CKD progression.